Enhanced therapeutic efficacy of Eupolyphaga sinensis Walker in females through sex-specific metabolomic-pharmacodynamic divergence - Chenghao Fei; Jie Zou; Zhaorui Yang; Huaiyang Chang; Lixian Lu; Kun Zhao; Hongzhuan Shi (Scientific Reports)
Abstract Eupolyphaga sinensis Walker (ESW), a medicinal insect used in traditional Chinese medicine, is renowned for its effects on blood circulation, stasis resolution, and bone and tendon healing. The underlying reasons for the clinical preference for female ESW remain unclear. Previous investigations were limited in scope, focusing narrowly on female specimens, large-molecule compounds, and single pharmacological effect. This study systematically compared female and male ESW in terms of composition and therapeutic efficacy. Metabolomics identified 31 compound types in both female and male ESW, including lipids, amino acids, and fatty acids. Female ESW exhibited significantly higher levels of 8 bioactive compounds, 15 small peptides, and 13 prostaglandins compared to male ESW, which contribute to immunity enhancement, antithrombotic effects, and improved bone metabolism. These differences may underlie the superior medicinal efficacy of female ESW. In the thrombosis model, ESW can cause vasodilation, reduce blood cell aggregation and thrombosis rate of mice tails. It also improved t-PA levels, prolonged APTT, and enhanced hepatic SOD activity, with female ESW showing stronger effects on MDA and D2D levels, indicating its stronger ability to protect cells from damage and fibrinolytic effect. In the osteoporosis model, ESW increased femur length, liver, and thymus indices while regulating serum BALP and Mg levels. Female ESW notably reduced TRACP-5b, OT/BGP, P, and Cu to normal levels, indicating its stronger ability to improved bone metabolism, corrected disturbances in calcium-phosphorus metabolism, and regulated serum inorganic elements. Overall, female ESW exhibited a greater abundance of bioactive components and demonstrated superior anti-thrombotic and anti-osteoporotic effects. These findings highlight the superior therapeutic effects of female ESW due to its enriched bioactive components, supporting its clinical preference while underscoring the potential of male ESW for uilization of resource.